2022
DOI: 10.4049/jimmunol.2100624
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 Deficiency Impacts on Plasmacytoid Dendritic Cells in Homeostasis and Autoimmune Disease

Abstract: Dendritic cells (DCs) are heterogeneous immune regulators involved in autoimmune diseases. Epigenomic mechanisms orchestrating DC development and DC subset diversification remain insufficiently understood but could be important to modulate DC fate for clinical purposes. By combining whole-genome methylation assessment with the analysis of mice expressing reduced DNA methyltransferase 1 levels, we show that distinct DNA methylation levels and patterns are required for the development of plasmacytoid DC and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Different DNA methylation levels and patterns are needed for the development of DC subsets, with pDC showing the highest DNA methylation levels across differentially methylated regions (DMRs) and most sensitive to hypomethylating perturbation. 416 , 417 DNMT1 deficiency leads to hypomethylation and upregulation of suppressor of cytokine signaling (SOCS)1 and impairs the maturation of tumor-associated DCs. 418 Meanwhile, TET2-mediated DNA demethylation along with the JAK3-STAT6 pathway is crucial for moDC differentiation upon IL-4 and GM-CSF stimulation, and elevating the enzymatic activity of TET2 by vitamin C treatment during the differentiation improves the immunogenic properties of moDCs, supporting the proliferation and function of T cells and the cancer immunotherapy.…”
Section: Methylation In Neurological Disorders Cancer and Agingmentioning
confidence: 99%
“…Different DNA methylation levels and patterns are needed for the development of DC subsets, with pDC showing the highest DNA methylation levels across differentially methylated regions (DMRs) and most sensitive to hypomethylating perturbation. 416 , 417 DNMT1 deficiency leads to hypomethylation and upregulation of suppressor of cytokine signaling (SOCS)1 and impairs the maturation of tumor-associated DCs. 418 Meanwhile, TET2-mediated DNA demethylation along with the JAK3-STAT6 pathway is crucial for moDC differentiation upon IL-4 and GM-CSF stimulation, and elevating the enzymatic activity of TET2 by vitamin C treatment during the differentiation improves the immunogenic properties of moDCs, supporting the proliferation and function of T cells and the cancer immunotherapy.…”
Section: Methylation In Neurological Disorders Cancer and Agingmentioning
confidence: 99%
“…In total, we identified 37,512 diffDMPs (Supplementary Table 5; Supplementary Table 6), of which 20,195 were found to be differentially methylated in more than one cell type ("shared diffDMPs") while 17,317 diffDMPs were exclusively identified in a single cell type ("unique diffDMPs"). During hematopoietic differentiation, DNA methylation changes were predominantly characterized by a loss of DNA methylation with 88% (15,278) of the unique diffDMPs and 74% (14,985) of the shared diffDMPs showing hypomethylation compared to HSPCs (Figure 3A). Gain of DNA methylation during differentiation from HSPCs to differentiated cell types was almost exclusively observed in cells of the lymphoid lineage (Figure 3A).…”
Section: Dna Methylation Dynamics During Murine Hematopoietic Differe...mentioning
confidence: 99%
“…The observation that DNMT3A is among the most frequently mutated genes in human acute myeloid leukemia (AML) [7,8] led to a variety of studies investigating the role of DNA methylation in healthy and malignant hematopoiesis [9][10][11][12][13][14][15]. An initial study using a custom array platform revealed global DNA methylation plasticity during murine progenitor differentiation and observed a global hypermethylation accompanying lymphoid lineage commitment [10].…”
Section: Introductionmentioning
confidence: 99%